2001
DOI: 10.1203/00006450-200112000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Fas and Fas Ligand Expression in Maternal Blood and in Umbilical Cord Blood in Preeclampsia

Abstract: The Fas-Fas ligand (FasL) pathway of apoptosis is abnormally activated in diseases associated with impaired immune tolerance or chronic inflammation. Pregnancy-related hypertension is a spectrum of disease that commonly causes significant morbidity in women and in their newborn infants, is associated with generalized inflammation, and may be causally related to impaired maternal-fetal tolerance. Our recent observation of enhanced trophoblast expression of FasL in one form of pregnancy-related hypertension led … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 56 publications
2
30
2
2
Order By: Relevance
“…Former reports on serum sCD95L predominantly revealed decreased levels in cord blood and during the neonatal period as compared with adults and pregnant women (29,30). In view of balancing inflammatory reactions in neonates, we therefore speculate that reduced levels of external death ligands such as CD95L might shift the balance toward prolonged inflammation by insufficient downregulation of immune effector cells, possibly leading to tissue destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Former reports on serum sCD95L predominantly revealed decreased levels in cord blood and during the neonatal period as compared with adults and pregnant women (29,30). In view of balancing inflammatory reactions in neonates, we therefore speculate that reduced levels of external death ligands such as CD95L might shift the balance toward prolonged inflammation by insufficient downregulation of immune effector cells, possibly leading to tissue destruction.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Nevertheless, there is evidence of changes in Fas and FasL that imply a role in preeclampsia. [9][10][11] Furthermore, Fas and FasL may also be involved in the hypertension of pregnancy as Koenig and Chegini reported differential expression of Fas and FasL in fetal membranes, decidua, and placentas from gestations with hypertension than in normal controls. 12 Matrix metalloproteinases are able to cleave FasL, leading to a soluble form measurable in plasma, as reported in preeclampsia, pregnancy, and in the syndrome of hemolysis, elevated liver enzymes, and low platelets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested an association between increased placental apoptosis and preeclampsia [10,26]. Increased trophoblast apoptosis reported in preeclampsia may be due to specific mechanisms, including TNF-α and TNF receptor superfamilies [28,29], inasmuch levels of TNF/ TNFR superfamily ligands and receptors [30][31][32] and other cytokines [30,33] stimulating apoptosis have been shown to be increased in preeclampsia. Our results showed an exaggeration of apoptosis in preeclamptic cytotrophoblasts and syncytiotrophoblasts and this is consistent with the findings of Cocker et al [27], who showed differences in apoptotic susceptibility of isolated cytotrophoblasts and syncytiotrophoblasts in pregnancy complicated with preeclampsia [27].…”
Section: Discussionmentioning
confidence: 95%